1980
DOI: 10.1182/blood.v56.3.516.bloodjournal563516
|View full text |Cite
|
Sign up to set email alerts
|

Result of attempted hematopoietic reconstitution using isologous, peripheral blood mononuclear cells: a case report

Abstract: In order to test the effect of peripheral blood mononuclear cell infusions on hematopoietic recovery in man we intensively leukapheresed a normal identical twin and obtained 9.8 x 10(10) peripheral blood mononuclear cells containing 4 x 10(5) CFU-C. These isologous cells were infused into his identical twin brother who had received 150 rad of total body irradiation and intensive combination chemotherapy as adjuvant therapy for Ewing's sarcoma. When compared to other patients receiving similar treatment, leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This is supported by similar findings for the mouse pluripotent progenitor cells CFUs, with circulating CFUs having a lower proliferation potential than their counterparts in the bone marrow (Micklem et al, 1975). Similarly the inferior repopulating ability of circulating as compared to bone marrow-derived normal human pluripotent haemopoietic progenitor cells in the treatment of marrow aplasia (Hershko et al, 1979;Abrams et al, 1980) could be explained by the relative lack of multipotent progenitor cells in peripheral blood found in this study.…”
Section: Discussionsupporting
confidence: 87%
“…This is supported by similar findings for the mouse pluripotent progenitor cells CFUs, with circulating CFUs having a lower proliferation potential than their counterparts in the bone marrow (Micklem et al, 1975). Similarly the inferior repopulating ability of circulating as compared to bone marrow-derived normal human pluripotent haemopoietic progenitor cells in the treatment of marrow aplasia (Hershko et al, 1979;Abrams et al, 1980) could be explained by the relative lack of multipotent progenitor cells in peripheral blood found in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The two reported attempts at haemopoietic reconstitution in man using peripheral blood cells from normal donors have failed (Hershko et al, 1979;Abrams et al, 1980), probably because an inadequate number of stem cells, as indicated by the CFU-GM content, was collected and infused. A preliminary study on an ANLL patient using discontinuous leukapheresis during early remission has been reported (Juttner et al, 1982b) and 4 x lo4 CFU-GM/kg body weight were cryopreserved but no systematic studies on the feasibility and safety of the procedure have been reported.…”
mentioning
confidence: 99%
“…(1 970) [75], Hershko et al (1979) [76] or Abrams et al (1980) [77] were not or only partially successful may well be due to the conditioning regimen on the one hand, and to the insufficient number and quality of stem and progenitor cells collected and transfused on the other. It, therefore, was the question for our group to analyze the regeneration pattern of granulocytes in patients receiving a myeloablative therapy for the treatment of hemopoietic malignancies, and subsequently a transfusion of blood-derived cryopreserved stem cells after appropriate blood stem cell expansion protocols.…”
Section: Hematopoietic Restoration After Blood Stem Cell Transfusion mentioning
confidence: 99%